Economic Evalvation of Pasture Establishments in Arid Region - Bhati, G N; Bhati, T K; Shankarnarayan, K A (Annals of Arid Zone, 2016)
Studies were conducted on grazing behaviour of mixed fiock of ram Jambs and he-goats at a fixed stocking rate of 10 animals ha-1 on shrub (Ziziphus nummularia) and legume (Clitorea ternateql based-pastures of buffel grass, Cenchrus ciliaris. Pure pastures of C.ciliaris were profitable and could recover investment cost in the second year, but in the long run, shrub based pasture showed a more productive trend. Shrub based pastures involved more investment cost for planting and maintenance of Ziziphus. Legume based pastures could not sustain the grazing stress and failed to regenerate under prevailing droughts of 1983-84.